Persistence of immunogenicity after seven COVID-19 vaccines given as third dose boosters following two doses of ChAdOx1 nCov-19 or BNT162b2 in the UK: Three month analyses of the COV-BOOST trial. Issue 6 (June 2022) - Liu, Xinxue; Munro, Alasdair P S; Feng, Shuo; Janani, Leila; Aley, Parvinder K; Babbage, Gavin; Baxter, David; Bula, Marcin; Cathie, Katrina; Chatterjee, Krishna; Dejnirattisai, Wanwisa; Dodd, Kate; et al.
Highlights: The persistence of humoral responses are different between vaccines. After ChAd/ChAd, mRNA vaccines still have the highest humoral response at day 84. After BNT/BNT viral-vector vaccines have comparable or even higher humoral response at D84 compared with homologous BNT boost schedule. Heterologous and homologous schedules have different kinetics of antibody titre decline by day 84 which appears to depend both on vaccine class and order of administration. Half dose BNT induced comparable levels of humoral and cellular responses at day 84 compared with full dose BNT. Abstract: Objectives: To evaluate the persistence of immunogenicity three months after third dose boosters. Methods: COV-BOOST is a multicentre, randomised, controlled, phase 2 trial of seven COVID-19 vaccines used as a third booster dose. The analysis was conducted using all randomised participants who were SARS-CoV-2 naïve during the study. Results: Amongst the 2883 participants randomised, there were 2422 SARS-CoV-2 naïve participants until D84 visit included in the analysis with median age of 70 (IQR: 30–94) years. In the participants who had two initial doses of ChAdOx1 nCov-19 (Oxford-AstraZeneca; hereafter referred to as ChAd), schedules using mRNA vaccines as third dose have the highest anti-spike IgG at D84 (e.g. geometric mean concentration of 8674 ELU/ml (95% CI: 7461–10, 085) following ChAd/ChAd/BNT162b2 (Pfizer-BioNtech, hearafter referred to as BNT)). However, in people who had two initial doses of BNT there was no significant difference at D84 in people given ChAd versus BNT (geometric mean ratio (GMR) of 0.95 (95%CI: 0.78, 1.15). Also, people given Ad26.COV2.S (Janssen; hereafter referred to as Ad26) as a third dose had significantly higher anti-spike IgG at D84 than BNT (GMR of 1.20, 95%CI: 1.01, 1.43). Responses at D84 between people who received BNT (15 μg) or BNT (30 μg) after ChAd/ChAd or BNT/BNT were similar, with anti-spike IgG GMRs of half-BNT (15 μg) versus BNT (30 μg) ranging between 0.74–0.86. The decay rate of cellular responses were similar between all the vaccine schedules and doses. Conclusions: 84 days after a third dose of COVID-19 vaccine the decay rates of humoral response were different between vaccines. Adenoviral vector vaccine anti-spike IgG concentrations at D84 following BNT/BNT initial doses were similar to or even higher than for a three dose (BNT/BNT/BNT) schedule. Half dose BNT immune responses were similar to full dose responses. While high antibody tires are desirable in situations of high transmission of new variants of concern, the maintenance of immune responses that confer long-lasting protection against severe disease or death is also of critical importance. Policymakers may also consider adenoviral vector, fractional dose of mRNA, or other non-mRNA vaccines as third doses.